Relevansi Hadis Nabi Tentang Pendidikan Anak Terhadap Peran Orang Tua dalam Membentuk Moral dan Etika Generasi Z - Fitri, Rafika; Muhajirin; Hedhri Nadhiran (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
In shaping the character of Generation Z, parents play the role of a captain who will guide individuals through the right path. The example set by the life of the Prophet Muhammad serves as the primary foundation for teaching children not only through words but also through actions and real practices. The discussions in this article are quite interesting, considering the technological and cultural developments that have led to a decline in moral and ethical values among children. Therefore, it is necessary to understand hadiths on educating children to enhance the moral character of Generation Z. By using qualitative analysis methods and the ma’anil hadis formulated by Yusuf al-Qardhawi, sourced from books and journals, it is hoped to analyze how the values present in hadith can be translated into the situations and conditions of parents in facing the current Generation Z. The research results conclude that there are several ways to shape the morals of children, especially Generation Z, namely starting character formation from when the child is still in the womb and applying what the Prophet Muhammad taught in educating his children. It is hoped that this can assist parents in shaping the character of Generation Z.